#TITLE_ALTERNATIVE# - RIYANTI (NIM : 12213052), RINDANG
Wax is a long-chained alkane able to become a solid under the temperature called wax appearance temperature (WAT). Wax deposition mitigation is so important to avoid production problems. It can be done using insulator and electric heater. Hence, the design of insulator and electric heater must be technically and economically optimum. This study proposes an efficient method to make the designing process easier. In this study, the mathematical model is made to construct the model. The main design principal for insulator and electric heater are similar by using heat transfer equation combined with economic equation. The method is then implemented for a field case. Then, the model is optimized to minimize cost by using GRG Nonlinear and Evolutionary optimization method. Optimization result for insulator design is included insulator thickness 1 in and length of insulation zone 19326.21 m. Meanwhile, the optimization result for electric heater is included the starting point of heater zone at 4665.69 m, length of heater zone 18334.31, and insulator thickness 1 in. This result is then evaluated by using a simulator that will be able to do more complex and realistic calculation. Therefore, this innovative method is proven to overcome the problem in planning the mitigation design for wax deposition. The design optimization in this study has been proven to successfully minimize the design cost with savings of 10.26% for insulator design and 13.54% for electric heating design, when compared with the cost of insulation and heating design for along the pipe length.